(3efgGL GdefGbH heYQGL GdMSjH GdKGbHs - (3eMeO Hf eSYhO Hf WjH Hf aQL GHf CHj GdNUGd NdUI GdZGabj, CHhYHO Gddg,J (B540 (3g` s
(3BNQgG (B:s
(3hEf GHfi GdYGUi gTGekG hUfhg Ydi fgL EjeGf efjQ eUhH s
(3hVYgG fXekG ai bUjOI ef GdHMQ GdWhjd Ydi Qhi GdHGAs
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B369 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B267 s
Keywords: (3GdJGQjNs